Peranan Disiplin dan Evaluasi Kerja untuk Meningkatkan Produktivitas Kinerja Karyawan Aston Batam Hotel & Residence - Fakhrul Rizal; Mardi Siswoyo; Fernandez Hutagalung; Rudianto Rudianto; Marisi Pakpahan (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
This research explores the significant role of discipline and work evaluation in improving employee performance at Aston Batam Hotel & Residence. The primary objective is to analyze how the enforcement of workplace discipline and the implementation of systematic performance evaluations influence productivity, service quality, and overall operational success within the hospitality sector. Employing a quantitative research methodology, data were collected through structured questionnaires and supported by performance records. The results indicate that discipline serves as a foundation for consistency, punctuality, and adherence to established organizational standards, while regular and structured work evaluations offer constructive feedback, identify strengths and weaknesses, and provide targeted development opportunities. The synergy between these two factors not only enhances individual employee performance but also contributes to a positive organizational culture and sustained service excellence. The study concludes that a well-balanced approach, combining firm disciplinary practices with continuous performance evaluation, is essential for fostering motivation, accountability, and long-term competitiveness in the hotel industry. Meanwhile, performance evaluations provide an ongoing feedback loop that allows management to identify areas for improvement and recognize top performers. By offering clear metrics and expectations, performance evaluations give employees the tools they need to improve and excel. The study also emphasizes the importance of a constructive evaluation approach that not only addresses shortcomings but also celebrates achievements, fostering a growth-oriented work environment. The synergy between these two factors not only enhances individual employee performance but also contributes to a positive organizational culture and sustained service excellence. When employees feel supported by regular evaluations and held accountable through discipline, they are more likely to take ownership of their roles and contribute to the hotel's long-term success.